Editorial Report on International Extension Education Conference BHU 2023 - Editorial Team (Indian Journal of Extension Education, 2023)
International Extension Education Conference, “IEEC BHU 2023” on “Innovative Applications of Agricultural Extension for Sustainable Food & Environmental Security” held at Banaras Hindu University, Varanasi (U. P.) India during 27-30 January, 2023.